THE COMPARISON OF ROAD CAPACITY OF GREENSHIELD MODEL, GREENBERG MODEL AND UNDERWOOD MODEL TOWARD MKJI 1997 CALCULATION ON THE JENDRAL SUDIRMAN ROAD, BATANG - Farhan Sholahudin; Abdul Rochim (Pondasi, 2019)
Jendral Sudirman road is one of the streets in Batang Regency which has function as primary artery and it has main access to connect vital locations. It makes Jendral Sudirman road has several transportation problems. In the planning, design and establishment of various transportation system policies, traffic flow theory of movement has very important role. To facilitate the application of traffic flow theory of movement used a mathematical approach which was used to analyze the phenomenon that took place in the traffic flow. One of approach ways to comprehend the traffic behavior was by verifying it into mathematical and graphics relationships with observing to the relationship among the speed (S), density (D) and volume (V) traffic.The objective of this study was to determine traffic flow characteristics on Jendral Sudirman Road consisting of three (3) main parameters such as volume, speed and density by using mathematical models included Greenshield, Greenberg and Underwood Model. In addition, this study also aimed to determine the results of a comparison of one of the chosen model with the road capacity calculation based on MKJI 1997.Based on the data analysis  by using Greenshield model, it was known that the characteristics of the traffic on Jendral Sudirman road values obtained free flow speed (Sf)= 45.53 km/h, density jam (Dj)= 38.31 unit/km and maximum volume or road capacity(Vmax)= 1774.25 unit/hour. The estimation result of model was calculated using Greenshield model and estimation capacity calculations of MKJI 1997 had a difference about 15.49%. This could be evidence that generalize the use of manual book as MKJI 1997 in estimating the value of a certain road location capacity without researching driver behavior, vehicle characteristics and the environment of the road would be at risk in the capacity estimation results obtained. Therefore, the use of existing guidelines such as the 1997 MKJI needs carefulness in assessing the environmental condition of the road and traffic characteristics.Keywords : TrafficCharacteristic, Volume, Speed, Density, Greenshield, Greenberg, Underwood